A cross-sectional study of ocular surface discomfort and corneal nerve dysfunction after paclitaxel treatment for cancer - Jeremy Chung Bo Chiang; David Goldstein; Terry Trinh; Kimberley Au; Susanna B. Park; Arun V. Krishnan; Maria Markoulli (Scientific Reports, 2021)
Abstract Ocular surface dysfunction is common in patients receiving anti-cancer drug treatment. The effects of paclitaxel, a neurotoxic chemotherapeutic drug, on ocular surface discomfort associated with dry eye disease was investigated. Patients with cancer who had completed paclitaxel treatment between 3 and 24 months prior to assessment (n = 29) and age- and sex-matched healthy control subjects (n = 29) were recruited and assessed with the Ocular Surface Disease Index (OSDI) to measure ocular surface discomfort. In-vivo corneal confocal microscopy was used to evaluate corneal nerve parameters in the right eye. Peripheral neurotoxicity was assessed using patient-reported outcomes and clinical grading scales. The paclitaxel group had significantly worse OSDI total scores compared with controls (Median, Md = 19.3 and Md = 0, p = 0.007, respectively). Corneal nerve fiber and inferior whorl lengths were reduced in the paclitaxel group compared with controls (14.2 ± 4.0 and 14.4 ± 4.0 mm/mm2 vs. 16.4 ± 4.0 and 16.9 ± 4.9 mm/mm2, respectively, p = 0.04). When analyzed by presence of peripheral neuropathy, paclitaxel-treated patients with neuropathy showed worse OSDI total scores compared to those without peripheral neuropathy post-treatment (p = 0.001) and healthy controls (p < 0.001). More severe ocular discomfort and worse visual function was associated with greater peripheral neurotoxicity symptoms (r = 0.60, p = 0.001) and neuropathy severity (r = 0.49, p = 0.008), respectively. Patients who have been treated with paclitaxel have a higher risk of ocular surface discomfort associated with dry eye disease, particularly those with peripheral neuropathy. Future longitudinal studies should investigate the clinical impact of corneal nerve reduction in dry eye disease.